Microbial Electrochemical Fluidized Bed Reactor: A Promising Solution for Removing Pollutants From Pharmaceutical Industrial Wastewater - Asensio, Yeray; Llorente, María; Sánchez-Gómez, Alejandro; Manchon, Carlos; Boltes, Karina; Esteve-Núñez, Abraham (Frontiers in Microbiology, 2021)
The capacity of electroactive bacteria to exchange electrons with electroconductive materials has been explored during the last two decades as part of a new field called electromicrobiology. Such microbial metabolism has been validated to enhance the bioremediation of wastewater pollutants. In contrast with standard materials like rods, plates, or felts made of graphite, we have explored the use of an alternative strategy using a fluid-like electrode as part of a microbial electrochemical fluidized bed reactor (ME-FBR). After verifying the low adsorption capacity of the pharma pollutants on the fluid-bed electrode (7.92±0.05% CBZ and 9.42±0.09% SMX), our system showed a remarkable capacity to outperform classical solutions for removing pollutants (more than 80%) from the pharma industry like carbamazepine (CBZ) and sulfamethoxazole (SMX). Moreover, the ME-FBR performance revealed the impact of selecting an anode potential by efficiently removing both pollutants at +200 mV. The high TOC removal efficiency also demonstrated that electrostimulation of electroactive bacteria in ME-FBR could overcome the expected microbial inhibition due to the presence of CBZ and SMX. Cyclic voltammograms revealed the successful electron transfer between microbial biofilm and the fluid-like electrode bed throughout the polarization tests. Finally, Vibrio fischeri-based ecotoxicity showed a 70% reduction after treating wastewater with a fluid-like anode (+400 mV), revealing the promising performance of this bioelectrochemical approach.